2016
DOI: 10.1186/s13046-016-0404-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain stereotactic biopsy flow cytometry for central nervous system lymphoma characterization: advantages and pitfalls

Abstract: BackgroundBrain stereotactic biopsy (SB) followed by conventional histopathology and immunohistochemistry (IHC) is the gold standard approach for primary central nervous system lymphoma (PCNSL) diagnosis. Flow cytometry (FCM) characterization of fine-needle aspiration cytology and core needle biopsies are increasingly utilized to diagnose lymphomas however, no biological data have been published on FCM characterization of fresh single cell suspension from PCNSL SB. The aim of this study was to establish the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Given the frequently rapid clinical deterioration in CNS lymphoma and the negative impact of a lower performance score on survival, according to the two largest validated prognostic models, early diagnosis is may improve prognosis . Similar findings were reported in a much smaller cohort of 18 stereotactic biopsies recently . Cordone et al found a significant agreement between flow cytometry and immunohistochemistry diagnosis ( P = 0.0034).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the frequently rapid clinical deterioration in CNS lymphoma and the negative impact of a lower performance score on survival, according to the two largest validated prognostic models, early diagnosis is may improve prognosis . Similar findings were reported in a much smaller cohort of 18 stereotactic biopsies recently . Cordone et al found a significant agreement between flow cytometry and immunohistochemistry diagnosis ( P = 0.0034).…”
Section: Discussionmentioning
confidence: 99%
“…They described a sensitivity and specificity of flow cytometry by immunophenotyping of 89% and 100%, respectively. In the 2/18 PCNSL biopsies not identified by flow cytometry more central necrosis was present, compared to biopsies with concordant results and both patients used corticosteroids prior to the biopsy . We did not find more central necrosis in our discordant biopsies and corticosteroid use did not differ between concordant and discordant pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials have illustrated their potent antitumor efficacy in systemic B cell malignancies, including peripheral diffuse large B cell lymphoma (DLBCL) (5, 6). Importantly, more than 90% of PCNSL are of the DLBCL subtype, expressing the surface antigen CD19 (7). Recently, a case report illustrated the complete remission of a secondary CNS lymphoma in a patient treated with anti-CD19 CAR T cells (8).…”
mentioning
confidence: 99%
“…We also note that intraoperative squash cytology provides both qualitative diagnosis as well as the opportunity for the pathology staff to request raw material for later flow cytometric analysis . Also, when the presence of a glioma is established, the neurosurgeon may be asked to obtain raw material for molecular genetic analysis, i.e.…”
Section: Discussionmentioning
confidence: 99%